Communication campaigns and sustainable development objectives: an experience report in private higher education - Santos, Rita de Cassia Silva dos [UNESP]; Guaraldo, Tamara de Souza Brandao [UNESP]; Bastos, Gloria (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2024)
This work presents an experience report on the development of information literacy on the Sustainable Development Goals, carried out at a private university in the city of Bauru, after the Covid-19 pandemic. Information literacy requires people to recognize when information is needed and to have the ability to locate, evaluate, and use that information. The qualitative methodological approach used action research. The work included proposals for solving problems, presenting projects, discussing search strategies and how to select sources, in addition to disseminating the work. The context examined enables the training of professional citizens and connects the university with the demands of the population. The students produced communication campaigns to publicize the SDGs to the community.
Keywords: Communication; public relations; social marketing; information literacy